(untitled) (International Journal of Engineering and Computer Science, 2015)
When users uses the usual software tools they must have to change many valued logical thinking (approximate reasoning) within the two-valued computer logic. Although the Structured Query Language (SQL) is a very influential tool, it is not easy to satisfy needs for data selection based on linguistic terms and degrees of truth. In this paper, we are attentive in flexible querying which is based on fuzzy set theory. Medina et al. have developed a server named fuzzy SQL, associate flexible queries and based on a theoretic model called GEFRED. For modelling the flexible queries alongwith the concept of fuzzy attributes, an addition of the SQL language named fuzzy SQL has been defined. The FRDB has already been well-defined by the user. In this paper, we prolong the work of medina et al. to implement a new architecture of fuzzy DBMS based on the GEFRED model. The architecture is built on the theory in which we handle the weak coupling with the DBMS SQL Server.